2018
DOI: 10.5334/jime.475
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Initiatives for Open Educational Practices at an Australian and a Brazilian University

Abstract: This paper explores some key developments in Open Educational Practices (OEP) in higher education in Australia and in Brazil. More specifically, it focuses on the analysis of two individual universities: the University of Tasmania, in Australia; and the Federal University of Paraná, in Brazil. They are both public and mostly face-to-face universities trying to engage with OEP to enhance their blended learning offerings, and more generally learning and teaching. However, these institutions are distinctive in te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…For instance, several research studies have pointed out that there are not enough details about how OEP can be implemented in higher education for teaching [18,19]. Bossu and Meier [20] reported that OEP have been applied in several countries like Brazil and Australia. However, no details were provided about how OEP were applied for teaching.…”
Section: Research Gap and The Purpose Of This Studymentioning
confidence: 99%
“…For instance, several research studies have pointed out that there are not enough details about how OEP can be implemented in higher education for teaching [18,19]. Bossu and Meier [20] reported that OEP have been applied in several countries like Brazil and Australia. However, no details were provided about how OEP were applied for teaching.…”
Section: Research Gap and The Purpose Of This Studymentioning
confidence: 99%